The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10549-010-1055-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin synergizes cisplatin sensitivity in basal-like breast cancer cells through up-regulation of p73

Abstract: Recent gene expression profiling studies have identified five breast cancer subtypes, of which the basal-like subtype is the most aggressive. Basal-like breast cancer poses serious clinical challenges as there are currently no targeted therapies available to treat it. Although there is increasing evidence that these tumors possess specific sensitivity to cisplatin, its success is often compromised due to its dose-limiting nephrotoxicity and the development of drug resistance. To overcome this limitation, our g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…For example, the mTOR inhibitor rapamycin activates TAp73-mediated gene expression and sensitizes aggressive cancer cells to CDDP treatment. 58,163 Pharmacological stimulation of AMP-activated protein kinase leads to accumulation of TAp73 in the nucleus via direct phosphorylation and causes apoptosis, however, only in the presence of p53. 164 Smallmolecule inhibitors of phosphatidylinositol 3′-kinase, AKT or prodigiosin disrupt the inhibitory effect of mutant p53 on TAp73.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the mTOR inhibitor rapamycin activates TAp73-mediated gene expression and sensitizes aggressive cancer cells to CDDP treatment. 58,163 Pharmacological stimulation of AMP-activated protein kinase leads to accumulation of TAp73 in the nucleus via direct phosphorylation and causes apoptosis, however, only in the presence of p53. 164 Smallmolecule inhibitors of phosphatidylinositol 3′-kinase, AKT or prodigiosin disrupt the inhibitory effect of mutant p53 on TAp73.…”
Section: Discussionmentioning
confidence: 99%
“…High-titer lentiviral stocks were generated by cotransfection with packaging plasmids psPAX2 (Addgene plasmid 12260) and envelope plasmids pMD2.G (Addgene plasmid 12259) into HEK-293T cells as reported previously (19)(20)(21)(22)(23). The shRNA target sequences for CYP1A1, CYP2S1, and CYP2W1 are shown in Supplementary Table S2.…”
Section: Lentiviral Production and Transductionmentioning
confidence: 99%
“…Earlier studies showed that both, p73 and chemical inhibitors of HDAC1, like suberoylanilide hydroxamic acid (SAHA), are capable to induce autophagy in addition to apoptosis [53, 54]. The mammalian target of rapamycin (mTOR), another protein with key functions in cell growth and proliferation, for example, is able to regulate p73, and treatment with rapamycin sensitizes highly aggressive breast cancer cells to cisplatin through upregulation of TAp73 [55-57]. Our results revealed that the levels of autophagy induction measured as autophagic flux represented by the ratio of autophagosomal microtubule-associated protein 1A/1B-light chain 3 (LC3-II) to cytosolic (LC3-I) protein, differed considerably between the viruses used in this study.…”
Section: Discussionmentioning
confidence: 99%